Dampak Media Sosial terhadap Perubahan Perilaku Sosial Ekonomi Petani di Desa Srigading Kabupaten Bantul - Rahmawati, Emma; Hadie, Varenna Faubiany; Siregar, Nurul Aldha Mauliddina; Sukarno, Taufan Daniarta; Cahyani, Dwi Endah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
Changes in social and economic behavior in society can be influenced by various factors, one of them can be caused by the development of technology and information such as social media. Srigading Village in Bantul Regency is one of the villages affected by social media, especially for some farmers in the village who initially planted onion commodities, then turned to plant flowers. This is due to the influence of social media that is able to create new markets for agriculture, that are packaged in the concept of agro-tourism which is agro-tourism. The purpose of this study aims is to analyze changes in social and economic behavior that occur as a result of the development of social media and saw the picture of farmer’s economic activities who had changed from conventional farming to agro-tourism. This research method uses quantitative methods through a descriptive approach. Data collection using questionnaires, interviews, observation, and study of literature. The population subjects in this study were onion farmers who switched to flower farmers. The results shown the shifting in farming cultivation into agro-tourism farming brought changes in the socio-economic life of farmers in Srigading Village. This can be seen from the increase in Increasing incomes and higher economic activities that make life prosperous were factors that make the farmers changed their business. Farmers use the internet and social media to gain ideas, develop, promote and sell their products. The economic picture of farmers can be seen from the production and marketing processes that are easier. Expanding their business means they increase the employment rate inside the village. There is also a change in the pattern of consumption of agricultural products.